The role of productivity, wages, demand, and exchange rates on export performance: Evidence from the Turkish manufacturing industry - Koluman, Ahmet; Kaplan, Fatih (Economic Journal of Emerging Markets, 2025)
Purpose — This study explores the determinants of export performance in the Turkish manufacturing industry by examining the effects of productivity, wages, demand, and sector-specific real effective exchange rates from 2006 to 2019.Methods — Using firm-level export data across 21 manufacturing sectors, the study applies a Fixed-Effects model with Driscoll-Kraay standard errors to address heteroscedasticity, autocorrelation, and cross-sectional dependence. Endogeneity concerns are mitigated using Two-Step System GMM estimation, complemented by Moment Quantile Regression (MQR) for robustness checks across the export distribution.Findings — The results reveal that higher productivity, increased wages, and stronger external demand significantly enhance exports, while currency appreciation adversely affects export performance. Productivity emerges as the most influential factor.Implication — Productivity enhancement, stable exchange rate management, and workforce development support export-driven growth. Targeted policies that strengthen sectoral competitiveness and expand foreign market access are essential for sustaining manufacturing exports.Originality — This study departs from traditional macro-level analyses by constructing sector-specific indices for real exchange rates and external demand. It offers a more granular and precise understanding of export dynamics. The methodological rigor combines static and dynamic panel estimators to ensure robustness and advance empirical insights into firm-level export behavior.